Body Weight Support Combined With Treadmill in the Rehabilitation of Parkinsonian Gait: A Review of Literature and New Data From a Controlled Study - Berra, Eliana; De Icco, Roberto; Avenali, Micol; Dagna, Carlotta; Cristina, Silvano; Pacchetti, Claudio; Fresia, Mauro; Sandrini, Giorgio; Tassorelli, Cristina (Frontiers in Neurology, 2019)
Background. Gait disorders represent disabling symptoms in Parkinson's Disease (PD). The effectiveness of rehabilitation treatment with Body Weight Support Treadmill Training (BWSTT) has been demonstrated in patients with stroke and spinal cord injuries, but limited data is available in PD. Aims. The aim of the study is to investigate the efficacy of BWSTT in the rehabilitation of gait in PD patients. Methods. Thirty-six PD inpatients were enrolled and performed rehabilitation treatment for 4 weeks, with daily sessions. Subjects were randomly divided into two groups: both groups underwent daily 40-minute sessions of traditional physiokinesitherapy followed by 20-minute sessions of overground gait training (Control group) or BWSTT (BWSTT group). The efficacy of BWSTT was evaluated with clinical scales and Computerized Gait Analysis (CGA). Patients were tested at baseline (T0) and at the end of the 4-week rehabilitation period (T1). Results. Both BWSTT and Control groups experienced a significant improvement in clinical scales as FIM and UPDRS and in gait parameters for both interventions. Even if we failed to detect any statistically significant differences between groups in the different clinical and gait parameters, the intragroup analysis captured a specific pattern of qualitative improvement associated to cadence and stride duration for the BWSTT group and to the swing/stance ratio for the Control Group. Four patients with chronic pain or anxious symptoms did not tolerate BWSTT. Conclusions. BWSTT and traditional rehabilitation treatment are both effective in improving clinical motor functions and kinematic gait parameters. BWSTT may represent an option in PD patients with specific symptoms that limit traditional overground gait training, e.g. severe postural instability, balance disorder, orthostatic hypotension. BWSTT is generally well tolerated, though caution is needed in subjects with chronic pain or with anxious symptoms.